N-acetyltransferase 2 Slow Acetylator Genotype Associated with Adverse Effects of Sulfasalazine in the Treatment of Inflammatory Bowel Disease - Min Chen; Bing Xia; Bixiao Chen; Qiusha Guo; Jin Li; Mei Ye; Zhengguo Hu (Canadian Journal of Gastroenterology)
AIM: N-acetyltransferase 2 (NAT2) is an important enzyme catalyzing N-acetylation of sulfasalazine (SASP). The aim of the present study was to investigate associations of the genotypes of NAT2 with inflammatory bowel disease (IBD), and with adverse effects of SASP, which is used as the first-line treatment of IBD.